Interventions to improve the use of EMRs in primary health care: a systematic review and meta-analysis. Issue 1 (17th April 2019) - Hamade, Noura; Terry, Amanda; Malvankar-Mehta, Monali
Abstract : Background: Electronic medical record (EMR) adoption in primary care has grown exponentially since their introduction in the 1970s. However, without their proper use benefits cannot be achieved. This includes: 1) the complete and safe documentation of patient information; 2) improved coordination of care; 3) reduced errors and 4) more involved patients. The use of EMRs is defined by practitioners using EMRs and their features to perform daily practice functions. Objective: The purpose of this systematic review was to identify interventions aimed at improving EMR use in primary healthcare settings. Methods: Ten online databases were searched to identify studies conducted in primary healthcare settings aimed at implementing interventions to observe the use of EMRs and directly measure the use of EMR functions or outcomes effected by the use of EMR functions. Results: Of 2098 identified studies, 12 were included in the review. Results showed that interventions focused on the use of EMR functions, including referrals, electronic communication, reminders, use of clinical decision support systems and workflow management support functions, were five times more likely to show improvements in EMR use compared with controls. Interventions focused on data quality were five and a half times more likely to show improvements in EMR use compared with controls. Conclusions: Individuals in primary healthcare settings aiming to improve EMR use would benefit from implementing interventions focused on EMR feature add-ons such as clinical decision support systems and customised referral templates, and provisions of educational materials, or financial incentives targeted at improving the use of EMR functions and data quality.